Tinjauan Produk Cendera Mata Berdasarkan Prinsip–Prinsip Kerajinan pada Kampung Peunayong di Kecamatan Kuta Alam - Annisa Fitria; Mesra Mesra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research was conducted on 5 types of souvenirs taken from 4 shops in the Aceh market in Penunayong Village. This type of research is a qualitative descriptive study by describing the souvenirs studied and assessed based on the principles of craft. Sources of data in this study are documentation, literature and interviews. Data collection procedures were carried out through observation, interviews and documentation. The findings of this study indicate that overall the souvenirs have a fairly good value, in terms of unity, balance, emphasis and proportion. Obtained an average value of 73.35 in the category B value (good). From the three assessment teams, the average score was 230.75. So, obtained an average value of 76.91 in the category B value (good).